A quantitative analysis of bone lamellarity and bone collagen linearity induced by distinct dosing and frequencies of teriparatide administration in ovariectomized rats and monkeys. (8th June 2021) - Sato, Takanori; Takakura, Aya; Lee, Ji-Won; Tokunaga, Kazuaki; Matsumori, Haruka; Takao-Kawabata, Ryoko; Iimura, Tadahiro
Abstract: The lamellar structure of bone, which endows biomechanical rigidity to support the host organism, is observed in mammals, including humans. It is therefore essential to develop a quantitative analysis to evaluate the lamellarity of bone, which would especially be useful for the pharmacological evaluation of anti-osteoporotic drugs. This study applied a current system for the semi-automatic recognition of fluorescence signals to the analysis of un-decalcified bone sections from rat and monkey specimens treated with teriparatide (TPTD). Our analyses on bone formation pattern and collagen topology indicated that TPTD augmented bone lamellarity and bone collagen linearity, which were possibly associated with the recovery of collagen cross-linking, thus endowing bone rigidity.